2023
DOI: 10.5430/wjel.v13n7p355
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Experiences for Speaking Activities among Malaysian Undergraduate ESL Students

Syahwil Saputra,
Mohd Haniff Mohd Tahir,
Intan Safinas Mohd Ariff Albakri
et al.

Abstract: Speaking practice is crucial for ESL (English as a Second Language) students. Nevertheless, accomplishing speaking activities via online learning might be difficult for the college students at universities in Malaysia as they are non-native English speakers. There have been several studies about students' perceptions and preferences on online learning. Nonetheless, there was only a little research conducted to ascertain deep online learning perceptions and preferences of the undergraduate ESL students in Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Some of the teachers were worried that they might be looked at as less proficient if they made mistakes in their speeches such as mispronouncing words or committing grammar errors in the presentations. This contradicts the findings in studies conducted by (Saputra et al, 2023;Shukor & Madzlan, 2022;Zulkepli et al, 2018). In the study by Shukor and Madzlan (2022) which explored the use of vlogs in managing anxiety, they found that vlogs can be beneficial for reducing anxiety among ESL learners.…”
Section: Discussionmentioning
confidence: 59%
“…Some of the teachers were worried that they might be looked at as less proficient if they made mistakes in their speeches such as mispronouncing words or committing grammar errors in the presentations. This contradicts the findings in studies conducted by (Saputra et al, 2023;Shukor & Madzlan, 2022;Zulkepli et al, 2018). In the study by Shukor and Madzlan (2022) which explored the use of vlogs in managing anxiety, they found that vlogs can be beneficial for reducing anxiety among ESL learners.…”
Section: Discussionmentioning
confidence: 59%
“…In learning English vocabulary, learners often resort to rote memorization, associating English words with their native language equivalents, which can lead to confusion and misuse (Gairns & Redman, 1986). Historically, teaching methods prioritized grammatical structure, but the communicative approach, emerging in the 1970s, shifted focus to vocabulary acquisition for effective communication (Thornbury, 2002;Carter, 2012;Saputra et al, 2023). This shift underscores the importance of vocabulary in language learning and usage, as highlighted by scholars (Allen, 1983).…”
Section: Introduce the Problemmentioning
confidence: 99%